The Impact of High Waves on the Socio-Economic Conditions of Coastal Communities in Nusa Layn Hamlet, Asilulu Village, Leihitu Subdistrict, Maluku Tengah Regency - Nur Hasna Ely; Wiclif Sephnath Pinoa; Roberth Berthy Riry (Jurnal Pendidikan Geografi Unpatti, 2024)
This study aims to analyze the impact of high waves on the socioeconomic conditions of coastal communities in Dusun Nusa Lay, Asilulu Village, Leihitu District, Central Maluku Regency. The community in this area largely relies on the sea as their primary source of income, but high waves often disrupt their fishing activities, significantly affecting their economic and social well-being. This research utilized primary data obtained through questionnaires, interviews, and direct observations, as well as secondary data from relevant literature. The sample consisted of 30 heads of households directly involved in fishing activities. Analysis was conducted using descriptive statistics and simple linear regression tests to measure the impact of high waves on the income, education, health, and transportation of the community. The results show that high waves have a significant impact on the decline in income, accessibility to education, health, and transportation for coastal communities. Additionally, high waves increase the social and psychological pressures experienced by the community. In conclusion, mitigation efforts involving infrastructure improvement, education, and government policy interventions are necessary to enhance the resilience of coastal communities against the impacts of high waves and climate change.